Chemical Separation of Uranium and Precise Measurement of 234U/238U and 235U/238U Ratios in Soil Samples Using Multi Collector Inductively Coupled Plasma Mass Spectrometry - Veerasamy, Nimelan; Takamasa, Asako; Murugan, Rajamanickam; Kasar, Sharayu; Aono, Tatsuo; Inoue, Kazumasa; Fukushi, Masahiro; Sahoo, Sarata Kumar (Molecules (Basel, Switzerland), 2020)
A new chemical separation has been developed to isolate uranium (U) using two UTEVA columns to minimize iron and thorium interferences from high background area soil samples containing minerals like monazites and ilmenite. The separation method was successfully verified in some certified reference materials (CRMs), for example, JSd-2, JLk-1, JB-1 and JB-3. The same method was applied for purification of U in Fukushima soil samples affected by the Fukushima dai-ichi nuclear power station (FDNPS) accident. Precise and accurate measurement of 234U/238U and 235U/238U isotope ratios in chemically separated U were carried out using a multi-collector inductively coupled plasma mass spectrometer (MC-ICP-MS). In this mass spectrometric method, an array of two Faraday cups (1011 Ω, 1012 Ω resistor) and a Daly detector were simultaneously employed. The precision of U isotope ratios in an in-house standard was evaluated by replicate measurement. Relative standard deviation (RSD) of 234U/238U and 235U/238U were found to be 0.094% (2σ) and 0.590% (2σ), respectively. This method has been validated using a standard reference material SRM 4350B, sediment sample. The replicate measurements of 234U/238U in SRM shows 0.7% (RSD). This developed method is suitable for separation of U and its isotope ratio measurement in environmental samples.